Integration of blockchain and cryptographic algorithms for education certification and verification: a systematic literature - Roy Mubarak; Imam Riadi; Tole Sutikno (SHM Publisher, 2026)
Personal data has become a highly valuable asset in the digital era. The background of this research is the urgent need to raise awareness in the digital era about the importance of protecting digital education certificate. The purpose of this research is to analyze the integration of blockchain technology with cryptographic algorithms for the secure storage and verification of digital education certificates. The methodology follows the Prisma framework, which is carried out through four systematic stages: formulating research question, preparation research protocol, identification of records from four major databases (Google Scholar, IEEE, Springer, and MDPI) published between 2023 and 2026, screening of titles and abstracts to eliminate duplicate and irrelevant studies, eligibility assessment through full-text review based on predetermined inclusion and exclusion criteria, data extraction and validation for qualitative synthesis, and finally of 21 papers for analysis result, conclusion, limitation of research, research gap and novelty. The findings demonstrate that storage efficiency, verification speed, encryption diversity, fraud prevention and identity standards. The conclusion of this study is that a collaborative framework integrating blockchain with cryptographic techniques for the security and verification of digital education certificates, with a robust process, can create a robust and adaptive system against certificate forgery. This study provides conceptual and practical knowledge for developing a more comprehensive education certificate security framework.